The changing relationship between the academic profession and universities in Finnish higher education - Siekkinen, Taru (2019)
This doctoral dissertation describes how the relationship between the academic profession and universities has changed, and how the global trends, particularly New Public Management (NPM), managerialism and academic capitalism, as well as other societal expectations have influenced it in Finnish higher education. Prior studies show that these global trends have had various effects on academic profession. Additionally, they have driven universities to develop as an organisation. NPM and managerialism emphasise hierarchical management structures, control, performance evaluations, and efficiency, which are commonly incompatible with professional values and practices; collegial decision-making, autonomy and trust. Higher education institutions are also expected to have more relevance in their activities. In addition, academics have started to apply entrepreneurial and commercial ways of acting in their work. The data of this study were collected in Finnish universities, and in two projects that include two sets of survey data (from fixed-term academics and middle managers) and one set of interview data (from top and middle managers). Three empirical sub-studies incorporated in this research include perspectives from reciprocal commitment in academic careers, recruitments in universities, and change and continuity in the academic profession. The results suggest that the relationship between the academic profession and universities is often tense. The academic profession is a powerful professional group that protects its traditional practices, values and autonomy. Universities have faced external pressure to develop as an organisation, and started to control their staff and monitor their performance more strictly. This has questioned the reciprocity between academics and universities by academics, standardised the university structures and processes, and emphasised the power of middle-managers in universities. The short project-based funding has also made academic careers more insecure. This study also suggests that in the new institutional frameworks, academics have adapted new roles and identities, as they have been affected by new organisational and societal expectations. New type of connected academic professionalism is emerging as professional, organisational, and societal/entrepreneurial roles, and identities are being blended in academic work.